Patient Characteristics and Outcomes of a Provincial Prolonged-Ventilation Weaning Centre: A Retrospective Cohort Study - Louise Rose; Ian M Fraser (Canadian Respiratory Journal)
BACKGROUND: Growing numbers of critically ill patients require prolonged mechanical ventilation and experience difficulty with weaning. Specialized centres may facilitate weaning through focused interprofessional expertise with an emphasis on rehabilitation.